(untitled) (Research, Society and Development, 2021)
In the last two decades, Brazil has experienced several processes of structural changes in the field of Education, associated with social, political, economic, and cultural transformations that culminated in the expansion of the National Education System. The inclusion of people with disabilities in Higher Education has been defined as a State policy; however, much still needs to be made so that there is an effective inclusion of people with disabilities. In the present study, we carried out a systematic review to highlight issues related to the perception of the process of inclusion of people with disabilities in Higher Education. To this end, a systematic literature review was carried out with a search for articles in the Lilacs, PubMed, Scielo, Scopus, and Web of Science databases, selecting articles published between 2016 and 2020, using the terms of reference “Pessoas com Deficiência”, “Educação Especial” and “Ensino Superior” in Portuguese and “Disabled Persons”, “Education, Special” and “Education, Graduate” in English. Five articles were selected, addressing aspects of legislation and student/teacher perception about the studied topic. The findings indicate that inclusion as a process aimed at reducing inequalities in Higher Education emerges as an important public policy, with a great lack of both the architectural adequacy of the Institutions and the adequacy of pedagogical practices and qualified teacher training to provide the required support by the students. Approaches aimed at adequate inclusion must be implemented by Higher Education Institutions, public or private, in order to guarantee equal opportunities for people with disabilities in relation to other students.